Social Media Facebook in Rural Communities (Case Study of Bandar Klippa Village Community against Changes in Communication Psychology) - Akbar Aldi Kautsar; Mailin; Ade Soraya; Mas Khairani (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
This research is entitled "Facebook Social Media in Rural Communities (case study of Bandar Klippa Village Community against Changes in Communication Psychology)". This study aims to determine the psychological effect of rural community communication on social media Facebook and to find out what are the research criteria for rural communities in choosing social media. The time of the research was carried out from December 2, 2021 – December 10, 2021. The theories that support this research include: Media, Social Media, Facebook, and Village Community. This study uses a qualitative research method (Case Study). The population in this study is the Bandar Klippa Village Community.